Lactobacillus nagelii sp. nov., an organism isolated from a partially fermented wine - Edwards, Charles G. (2000)
A Gram-positive rod was isolated from a commercial grape wine undergoing a sluggish/stuck alcoholic fermentation. The organism produced D-L-lactic acid from glucose without gas formation, produced dextran from sucrose, hydrolysed aesculin and fermented galactose, D-glucose, D-fructose, D- mannose, L-sorbose, rhamnose, mannitol, sorbitol, methyl α-D-glucoside, N- acetylglucosamine, amygdalin, salicin, cellobiose, maltose, sucrose, trehalose and β-gentiobiose. 16S rRNA gene sequence analysis revealed that the isolate was phylogenetically a member of the genus Lactobacillus and formed a distinct subline within the Lactobacillus casei cluster of species. On the basis of phenotypic and phylogenetic evidence, Lactobacillus nagelii sp. nov. ATCC 700692(T) is proposed as a new species.